2018
DOI: 10.4172/2472-1220.1000171
|View full text |Cite
|
Sign up to set email alerts
|

Successful Renal Re-transplant in a Patient with Alport Syndrome: A Case Report

Abstract: This case report is of a sensitized patient with Alport syndrome, who received second kidney transplant from HLA-DQB1 incompatible living donor after excluding two unrelated donors. Four months after transplant he developed BK virus allograft nephropathy, from which he recovered and has excellent renal function-four years posttransplant. The findings highlight that HLA incompatible renal transplant can be performed successfully with prudent pre, and post-transplant evaluation complemented by suitable immunosup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“… 15 Several reports have found that the BK virus (BKV) allograft neuropathy (1 - 10%) and the cytomegalovirus (CMV) infection contribute significantly to retransplant. 16 , 17 , 18 In our study, during the follow-up, monitoring of the patients for infectious markers was performed and 4 cases were found to have an infection, CMV (1 patient), BKV (1 patient) and pneumonia (in 2 patients).…”
Section: Discussionmentioning
confidence: 82%
“… 15 Several reports have found that the BK virus (BKV) allograft neuropathy (1 - 10%) and the cytomegalovirus (CMV) infection contribute significantly to retransplant. 16 , 17 , 18 In our study, during the follow-up, monitoring of the patients for infectious markers was performed and 4 cases were found to have an infection, CMV (1 patient), BKV (1 patient) and pneumonia (in 2 patients).…”
Section: Discussionmentioning
confidence: 82%